Inteligência analítica: competências para atuação - Ruggiero, Pedro Henrique Gomes (2017)
In the era of Big Data, the area of Business Intelligence and Analytics has become increasingly important for academic communities as well as for the market. Most researchers believe that it is necessary to train and train professionals with a set of skills in technologies, techniques and business, but there is little understanding and convergence on this set. The objective of this paper is to list and describe, according to the literature, a set of competencies to perform in Business Intelligence and Analytics, since there are many complementary studies and with different answers. Focusing on this objective, an analysis of citations was carried out to collect a base of texts that were the scope of the work; An analysis in these texts, from the perspective of the Theory of Competences, to find the competences; A validation with specialists, in order to diminish the subjectivity of the use of the Theory of Competences; And a frequency count of competencies validated throughout the text base, to obtain material and to describe those competencies. A unified set of skills was determined, between knowledge, skills and behavior. For researchers, the result of this work serves as a unified basis of competences and their descriptions, which could be used to carry out numerous more advanced studies and directed towards the use of Business Intelligence and Analytics. For business managers, the result of this work could be used to select professionals to perform in Business Intelligence and Analytics, or to develop internal training, among others.